MEMBANGUN KARAKTER KRISTIANI MELALUI PENDIDIKAN AGAMA KRISTEN DI ERA DIGITAL TANTANGAN DAN STRATEGI IMPLEMENTASI DI SEKOLAH - Yuris Tandi Panga; Adelvia ponno bua'; Jumiati Petrus Sulu; Ferorewanti; Mince Rupi (ADIBA : JOURNAL OF EDUCATION, 2025)
This article discusses the urgency of Christian Religious Education (PAK) as a means of developing students' Christian character in the digital era. The transformation of information technology has had a significant impact on the way young people think and act, including in terms of morality and spirituality. Challenges such as low interest in religious studies, the dominance of digital culture, and teachers' limited digital competencies hinder the effective implementation of PAK. Therefore, innovative learning strategies are needed, such as a project-based approach, faith reflection, and the wise use of technology to support the internalization of Christian values. Furthermore, synergy between schools, families, and churches is crucial in creating a holistic and consistent character-building ecosystem. With a holistic approach, PAK can be a transformative force in shaping a generation that is resilient in faith and character amidst the rapid flow of digitalization.